A review of drug addiction and influential factors in university students - Hacıhasanoğlu, Rabia; Türkleş, Serpil (Journal of Dependence, 2009)
Objective: This study was carried out to analyze drug addiction and influential factors in students attending Erzincan School of Law, Faculty of Science and Literature, Health School and Vocational School at Atatürk University. Method: The universe of this descriptive and cross-sectional study comprised a total of 4377 students who attended the above mentioned schools and the sampling comprised 963 students(22%oftheuniverse) randomly chosen among them. The data were collected in May 2005 through a descriptive form designed by the investigators and were evaluated using percentage calculationsand chi-square test. Results: It was determined that 38.5% of the students smoked, 18.2% used alcohol, and 0.8% used volatile substance. It was established that the factors such as age and gender of the student, the place where the student lived, whether the student shared his/her problems with his/ her family and the profession of the father had an impact on smoking; gender of the student, the place where the student lived, whether the student shared his/her problems with his/her family, educational status and the profession of the mother, had an impact on the use of alcohol. Conclusion: Although the prevalence of use of cigarettes and alcohol and drug abuse is not very high, it is not at a desired level either. It is therefore recommendable that alternative programs be established for university students and relevant education provided to make them more resistant against drug addiction.